Aplikasi Go Food dan Gambaran Konsumsi Makanan Pada Mahasiswa - Fatmawaty Suaib; Aswita Amir (Jurusan Gizi Poltekkes Kemenkes Makassar, 2020)
AbstractGo Food is one of the many technological advances used by students because go food offers convenience in purchasing food / drinks. This was also put to good use by the Makassar Poltekkes Students. This utilization needs to be examined, if this utilization is used wisely which does not cause excessive consumption of food / drinks. This paper is wetting the description of staple foods and snacks ordered by students using the SQ-FFQ measurement tool. The results showed that in general, students only used very little go food to get staple foods and snacks every day, where they got staple foods and snacks outside of go food. Even so, the most popular staple food menu is processed fried chicken that has been packaged with rice. Their favorite snack menu is processed fried bananas mixed with chocolate or cheese and martabak and bright moon. The dental and pharmacy department is the department that has the highest number of orders than any other department, which is three times more than the obstetrics department for staple foods and five times that of the nursing department. The interesting thing about nutrition department has the third highest number of orders in the snacks category.